394 CARDIAC REPAIR UNDER CARDIOPULMONARY BYPASS IN CHILDREN WITH END-STAGE LIVER DISEASE. (1st January 2005) - Wu, J.; Laks, H.; Banerji, A.; Halnon, N.; Drant, S.; Odim, J.
Abstract : Background: Cardiac surgery for congenital heart disease in children awaiting liver transplantation presents unique therapeutic challenges and dilemmas. We tested the hypothesis that operations in these children requiring cardiopulmonary bypass (CPB) were not associated with prohibitive morbidity and mortality. Methods: Over the last 10 years (1994-2004), five infants were identified in our database with end-stage liver disease and awaiting liver transplantation who required cardiac surgery. Primary endpoint for the study was mortality. Secondary endpoints included morbidity and time to liver transplantation. (Table ) The new Pediatric End-Stage Liver Disease (PELD) model was used to score liver disease severity. Results: Three boys and two girls with mean age of 8.6 (range, 1.5-21mo) and mean PELD of 18.0 (range, 10-29) required CPB for repair. The only early mortality in the series occurred after cardiac arrest during initial off-pump creation of a central shunt later completed on CPB. The patient expired two days later despite extracorporeal membrane oxygenation support. The patient had important myocardial hypertrophy. All other patients survived and underwent successful liver transplantation. Conclusions: Children with important congenital heart disease awaiting liver transplantation can undergo safe cardiac repair with judicious peri-operative support thereby reducing the risks of subsequent liver transplantation.